An experimental study on the effect of systemic functional linguistics applied through a genre-pedagogy approach to teaching writing - Horverak, May Olaug (Yearbook of the Poznan Linguistic Meeting, 2016)
In the tradition of teaching English as a second language, there has been an increased interest in how functional language descriptions and understandings of genres may be used as resources for making meaning. The present study investigates what impact writing instruction that draws upon systemic functional linguistics (SFL) applied through a genre-pedagogy approach has on students’ ability to write argumentative essays. This includes explicit grammar instruction inspired by SFL, as well as instruction on text structure. The study uses a mixed-methods approach, with a quasi-experiment followed up by quantitative and qualitative analyses of the collected material. Statistical analyses indicate a significant positive effect on writing performance in the intervention groups, regardless of gender, first language and previous level of writing. As the study lacks control groups, the quantitative analysis was complemented with examples from student texts to illustrate the improvement revealed in the statistical analysis. The findings suggest that SFL applied through a genre-pedagogy approach to teaching writing may help students to improve their writing skills.